Languages of Love and Hate - Lambert, Sarah; Nicholson, Helen (Brepols, 2012)
This book probes the nature of the clash of cultures as a process of identification and classification of the unknown. ‘There is no world of thought that is not a world of language and one sees of the world only what is provided for by language’ (Walter Benjamin, 1936). In the medieval Mediterranean, cultural groups were frequently labelled, fixed, and identified by language, and these linguistic groupings were consistently in states of conflict and/or exchange. This collection explores various expressions of cultural clash and exchange, and examines some of the ways in which language was used to express difference, to mark out cultural difference, and to further label those cultures – often as alien and inferior, but sometimes as different and worthy of respect. This theme unites papers coming from a range of perspectives and engaging with a whole series of cultural interchanges and conflicts. It brings together work on a wide range of peoples – Latins, Byzantines, Muslims, and Jews – commenting on and writing about each other, as well as a wide variety of different genres, from theology to farce. This volume seeks to offer a broad and wide-ranging approach to understanding the world at the time of the crusades through the words of participants and observers.